Control augmentation design of UAVs based on deviation modification of aerodynamic focus - Shi, Y.; Li, R.; Xu, Honglei (2015)
Based on the analysis of force and action points of an UAV (unmanned aerial vehicle), we propose a concept called static stability degree deviation (SSDD) factor, which is related to the focus position, and can be used to modify the data for control law design. Furthermore, a SSDD-based method is presented to avoid the fight oscillation caused by the data deviation of aerodynamic focus. By using the attitude angle difference between real fight data and simulation data as an optimization index, the identification of SSDD factor and the data reproduction of the real fight data are achieved. The identification results are then used to modify aerodynamic blowing data. Based on the modified model, the augmentation control is designed by applying the altitude angle rate feedback to improve the equivalent damping ratio and frequency; thus the iteration design of the control law is performed.